MENGAPA ANAK BERKEBUTUHAN KHUSUS KELAS IV SD MENGALAMI KESULITAN MEMAHAMI GEOMETRI? - Khaeroni Khaeroni; Firas Faida Furti; M. Rifqi Rijal (Jurusan Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2023)
Children with Special Needs (ABK) in 4th grade at SDN Srengseng 04 West Jakarta have difficulty comprehending the material area and perimeter of geometric shapes. The study objective is to point out the contributing factors to these difficulties. This kind of examination is subjective with an elucidating approach. The methods of gathering data are Interviews, documentation, and observation. According to the findings, there are four categories of learning difficulties: learning disorders, learning disabilities, underachievers, and slow learners. Other factors that contribute to learning difficulties can be broadly separated into two kinds: internal factors and external factors. Physical and spiritual factors are internal factors, while family, school, and social environmental factors or the community around them are external factors. Two children with special needs were found to be slow learners and to have IQs that were below average, so the factors that influenced them were looked at. Additionally, it is hoped that, now that the causes of learning difficulties have been identified, the family and the school can come up with effective solutions